Rosacea treatments: Current standards and additional options. Issue 6 (29th September 2021) - Tan, Jerry; Singh, Balraj; Song, Yifeng; Zaher, Omar; Arents, Bernd W. M.; Schaller, Martin; van Zuuren, Esther J.
Abstract: Background: Rosacea, a chronic facial and ocular inflammatory disease, is readily visible with consequential adverse psychosocial impacts. Progress in epidemiology, pathophysiology, treatments, psychosocial and quality of life impact has led to improved outcomes. Additionally, there has been a transition to updated clinical criteria for diagnosis and classification, the phenotype approach, based on rosacea‐associated features. Objective: Our objective was to identify current evidence‐based standards of treatment for rosacea highlighting recently approved interventions and including innovative options. Methods: Reviews establishing current standards of care published over the past three years and English language clinical studies of rosacea treatment from 2018‐ March 2021 were included. In addition to pivotal trials, the latter were also selected based on innovation and practicality of the intervention. Results: In addition to treatments identified in guidelines and systematic reviews, additional options derive from use in other dermatological conditions ‐ such as botulinum toxin, hydroxychloroquine, photodynamic therapy, radiofrequency with or without microneedling ‐ or from other medical conditions, such as artemether and sumatriptan. Conclusion: We provide a template of longitudinal care for rosacea based on features divided into current standards and additional options. The latter may provide the impetus for further research and development to provide options with greater efficacy, longer remissions and/or lower risk of adverse events to improve outcomes in patients with rosacea.